2021
DOI: 10.3389/fspas.2021.647121
|View full text |Cite
|
Sign up to set email alerts
|

Influence of MHD Turbulence on Ion Kappa Distributions in the Earth's Plasma Sheet as a Function of Plasma β Parameter

Abstract: The possible influence of MHD turbulence on the energy distributions of ions in the Earth's plasma sheet was studied using data taken by the THEMIS satellites. Turbulence levels were traced using eddy diffusion coefficients (D), of which we measured one for each Geocentric Solar Magnetospheric (GSM) coordinates every 12 min. Ion fluxes between 1.75 and 210.5 keV during the same time windows that correspond to mainly suprathermal populations were fitted to Kappa distribution functions, which approximate a Maxwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…However, for P SW > 1 nPa the values of β in this local minimum start to be less than one, and—as shown experimentally by Eyelade, Espinoza, et al. (2021)—in this case for low β plasma the eddy diffusion might decrease the κ i . However, there is also strong evidence that at smaller scales the turbulence observed in the plasma sheet is dominated by electrostatic fluctuations (Ergun et al., 2018; Ovchinnikov et al., 2024).…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…However, for P SW > 1 nPa the values of β in this local minimum start to be less than one, and—as shown experimentally by Eyelade, Espinoza, et al. (2021)—in this case for low β plasma the eddy diffusion might decrease the κ i . However, there is also strong evidence that at smaller scales the turbulence observed in the plasma sheet is dominated by electrostatic fluctuations (Ergun et al., 2018; Ovchinnikov et al., 2024).…”
Section: Discussionsupporting
confidence: 50%
“…At the same time, Eyelade, Espinoza, et al. (2021) showed that depending on the value of plasma β , the ion κ index may decrease (low β ) or increase (high β ) with the eddy diffusion. For diffusion perpendicular to the plasma sheet, this change takes place for β ≈ 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a decrease of κ can mean the action of turbulent acceleration leading to the increase of the rigidity of ion spectra. The plasma sheet of the Earth is a region of intense velocity and magnetic field fluctuations (see the recent reviews of Antonova & Stepanova, 2021; Borovsky et al., 2020 and results of Eyelade, Espinoza, et al., 2021). The level of such fluctuations increases toward the tail and it is low at the distances <10RE during quiet geomagnetic conditions (Pinto et al., 2011; Stepanova et al., 2009, 2011).…”
Section: Discussionmentioning
confidence: 99%